INDEKS KEPUASAN MASYARAKAT DALAM PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN CIREBON - Subhan Subhan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2018)
One indicator to measure the success of public organizations that provide services to thecommunity is community satisfaction. Of course the problems that arise can be seen fromthe complaints felt by the recipient community. The purpose of this study was to find out:the index of community satisfaction with public services at the Cirebon RegencyPopulation and Civil Registry Service and the factors that influence the level of communitysatisfaction at Disdukcapil Cirebon District. The type of research used is descriptiveresearch, a study conducted to obtain a description/description of the implementation ofservice.Keywords: Public Service, Satisfaction Index, Disdukcapil